Three-dimensional tooth profile design method of harmonic drive considering the deformation difference of the flexspline. Issue 8 (17th February 2021) - Li, Yangfan; Zhang, Yingjie; Zhang, Ning; Xu, Bingchao
Abstract : Purpose: This paper aims to improve the meshing effect of the gear teeth. It is recommended to analyze the deformation difference between the inner and outer surfaces of the flexspline. The purpose of this paper is to modify the profile of the flexspline based on the deformation difference to improve the transmission accuracy and operating life of the harmonic drive. Design/methodology/approach: In this paper, ring theory is used to calculate the deformation difference of the inner and outer surfaces of the flexspline, and the actual tooth profile of the flexspline is corrected based on the deformation difference. Then, the flexspline is divided into multiple sections along the axial direction, so that the three-dimensional tooth profile of the flexspline is modified to improve the gear tooth meshing effect. Findings: This paper proves the effect of the deformation difference between the inner and outer surfaces of the flexspline on the tooth backlash, which affects the transmission accuracy and life of the harmonic drive. It is recommended to modify the tooth profile of the flexspline based on the deformation difference, so as to ensure the tooth meshing effect. Originality/value: This paper provides a new way for the optimization of the three-dimensional tooth profile design of the harmonic drive.